Biochemistry: A Short Course - Tymoczko J. L. John (International Edition)
The energy that the cyclists in the Tour of California need as they race along the coast connects them, by a series of metabolic pathways, to many other creatures. Most notably, photosynthetic organisms— the algae in the ocean, the plants on the hills, and their grain-crop relatives—provide the cyclists, and all life, with fuel and oxygen to power their lives. In this textbook, we examine the biochemical underpinnings of life and the molecules that sustain our every activity and help us to experience the world.